The Ecological Model of Pastures Zoning of Kurdistan Province Emphasizing on the Climatic Elements of Temperature and Precipitation - Gholamali Mozafari; Farshad Safarpour (جغرافیا و پایداری محیط)
Pastures are renewable natural resources which provide the grass for the cattle need, adjust the weather and hydrological flows, provide water for aquifer, prevent soil erosion, control pollution, dispel food poisoning, and bring about soil formation through improving soil formation processes. Classification of pastures with regard to the rate of grass production and paying fine to pasture owners in case of famine is one of the issues which have always been the focus of agricultural planners. Kurdistan province is one of the fertile regions for range management in Iran. In order to classify the pastures across the province, a database was established which contained data such as topographic maps, slope, highness levels, radiation direction map, geology, soil, plantation, hydrographic network and climatic layers of temperature and Precipitation. In this study the daily data of temperature and Precipitation were obtained in a statistical period of 19 years (1990-2009). All these informational layers were reweighted and reclassified based on the ecologic needs of pasture plants. Using Boolean logic in the Arc GIS environment, these layers were integrated and the classification maps of pasture Kurdistan province in 3 groups (rich, medium and poor) were provided. The results of the study showed that using the different informational layers corresponding ecological needs of pasture plants is an optimal method for providing an appropriate classification of pastures. 37824.2 hectare out of 2904642.7 hectare of the total area of Kurdistan province were classified as good with an exponentiation of degree 1, while 402891.3 hectare were classified as medium with an exponentiation of degree 2 and 411897.1 as poor with an exponentiation of degree 3.